SINERGI RAJA ALIM DAN THINK TANK-NYA: KERATON DAN PEMBENTUKAN TRADISI KEILMUAN ISLAM NUSANTARA - Multazami, Dawam (IAIN Ponorogo, 2015)
Abstrak:In general, theories about the arrival of Islam in this country came in the 7th century BC, by various methods and strategies of endeavors. The preacher came and tried to blend with the occupants by using native language and their customs, and then mate with the natives. Finally, they made small community to maintain friendship with the potentate. Palace or castle has an important role as part of forming the Islamic nation tradition. The close Relationship between parsons and potentate drawn in the role of co-operation through educational institutions outside the palace and in palace, the parsons are instructed to write scientific papers and served as state law, palace policies lifting parsons in strategic positions as mufti or qodhi, palace become a place to discuss intellectual matters and so forth. The relationship between palace and the forming of Islamic nation tradition depicted into some areas in this country such: the scientific tradition of Islam in Aceh Darussalam. Its began from meunasah (madrasah) in which students learned the Arabic alphabet, read al-Qur'an, prayer procedures, morality, monotheism study, fiqh study, tasawwuf study, the Islamic roles in building a mosque then used as a place of higher education. Collective leadership between sultan and Wali Songo in Demak Bintoro, Sultan Banjar attend to Islamic development through education build by Shaikh Arshad, and the establishment of Shari'ah courtKeywords: Raja Alim, Kesultanan Aceh, Musawaratan Wali dan Daeng Ta Kaliya.